THE TECTONICS OF PYLGA SUTURE ZONE (TAIGONOS PENINSULA, NORTHEASTERN ASIA) - Bondarenko G.E.; Morozov O.L.; Kravchenko-Berezhnoy I.R.; Silantiev S.A.; Khudoley A.Kh. (My University, 2000)
The Pylga Suture Zone is a kind of a suture zone between the Paleozoic-Mesozoic island-arc rocks of the Taigonos Peninsula and the Precambrian rock complexes of the Avekovo Block. This zone is distinguished by its intensive tectonic deformation, its compositionally specific igneous rock complexes, and dynamic metamorphism. Discussed in this paper is the tectonic evolution of the Pylga Zone, using the examples of its two segments: one in the Pylga R.-Bolshaya Chaibukha R. divide, the other at the Glinyanui Cape. The authors conclude that beginning from the Late Permian to the Early Jurassic, inclusive, the Pylga R. paleobasin was situated in the rear of the Koni-Taigonos ensialic island arc, being a part of some larger assemblage of back-arc structural features of rift origin. The region experienced a few periods of extension and compression, including the inferred period of Middle Cretaceous extension and the rising of the older rocks to the ground surface. The evolution of the Pylga-Inchik Zone was dominated by shear-type deformations.
Keywords: TECTONICS OF SUTURE ZONES; ISLAND-ARC ROCKS; TECTONIC DEFORMATION; TECTONIC EVOLUTION; SHEAR-TYPE DEFORMATIONS